The Existence of Indonesian Peasants in Three Eras: Dutch Colonialism, Japanese Colonialism, and The Independence - Saragih, Mujahid Widian; Hasibuan, Yandi Syahputra (Talenta Publisher, 2023)
This article discusses the existence of peasants during three eras with different powers. During the Dutch and the Japanese colonialism, it can be said that peasant is a profession that must be avoided because it will become an object of exploitation by those in power. During Dutch rule in Indonesia, the policies that exploited peasants were ‘culturstelseel’ (the forced planting system) and the 1870 Agrarian Law. These two policies made peasants even more impoverished, the lands that formerly owned peasants were forcibly taken away to plant commodities that were in demand on the world market and the profits went into their pockets ruler. During the Japanese colonialism, an obligation to produce rice made peasants increasingly tormented because they had to pursue predetermined targets. During The independence, the peasants were embraced by political parties until they were transformed into mass organizations. Although there has been some progress in the national agrarian political agenda, differences in ideology and interests have resulted in conflicts and struggles between peasant mass organizations, and even with civil society.